# 5.1: Homogeneous Linear Equations

A second order differential equation is said to be linear if it can be written as

[label{eq:5.1.1} y''+p(x)y'+q(x)y=f(x).]

We call the function (f) on the right a forcing function, since in physical applications it is often related to a force acting on some system modeled by the differential equation. We say that Equation ef{eq:5.1.1} is homogeneous if (fequiv0) or nonhomogeneous if (f otequiv0). Since these definitions are like the corresponding definitions in Section 2.1 for the linear first order equation

[label{eq:5.1.2} y'+p(x)y=f(x),]

it is natural to expect similarities between methods of solving Equation ef{eq:5.1.1} and Equation ef{eq:5.1.2}. However, solving Equation ef{eq:5.1.1} is more difficult than solving Equation ef{eq:5.1.2}. For example, while Theorem (PageIndex{1}) gives a formula for the general solution of Equation ef{eq:5.1.2} in the case where (fequiv0) and Theorem (PageIndex{2}) gives a formula for the case where (f otequiv0), there are no formulas for the general solution of Equation ef{eq:5.1.1} in either case. Therefore we must be content to solve linear second order equations of special forms.

In Section 2.1 we considered the homogeneous equation (y'+p(x)y=0) first, and then used a nontrivial solution of this equation to find the general solution of the nonhomogeneous equation (y'+p(x)y=f(x)). Although the progression from the homogeneous to the nonhomogeneous case isn’t that simple for the linear second order equation, it is still necessary to solve the homogeneous equation

[label{eq:5.1.3} y''+p(x)y'+q(x)y=0]

in order to solve the nonhomogeneous equation Equation ef{eq:5.1.1}. This section is devoted to Equation ef{eq:5.1.3}.

The next theorem gives sufficient conditions for existence and uniqueness of solutions of initial value problems for Equation ef{eq:5.1.3}. We omit the proof.

Theorem (PageIndex{1})

Suppose (p) and (q) are continuous on an open interval ((a,b),) let (x_0) be any point in ((a,b),) and let (k_0) and (k_1) be arbitrary real numbers(.) Then the initial value problem

[y''+p(x)y'+q(x)y=0, y(x_0)=k_0, y'(x_0)=k_1 onumber ]

has a unique solution on ((a,b).)

Since (yequiv0) is obviously a solution of Equation ef{eq:5.1.3} we call it the trivial solution. Any other solution is nontrivial. Under the assumptions of Theorem (PageIndex{1}), the only solution of the initial value problem

[y''+p(x)y'+q(x)y=0, y(x_0)=0, y'(x_0)=0 onumber ]

on ((a,b)) is the trivial solution (Exercise 5.1.24).

The next three examples illustrate concepts that we’ll develop later in this section. You shouldn’t be concerned with how to find the given solutions of the equations in these examples. This will be explained in later sections.

Example (PageIndex{1})

The coefficients of (y') and (y) in

[label{eq:5.1.4} y''-y=0]

are the constant functions (pequiv0) and (qequiv-1), which are continuous on ((-infty,infty)). Therefore Theorem (PageIndex{1}) implies that every initial value problem for Equation ef{eq:5.1.4} has a unique solution on ((-infty,infty)).

1. Verify that (y_1=e^x) and (y_2=e^{-x}) are solutions of Equation ef{eq:5.1.4} on ((-infty,infty)).
2. Verify that if (c_1) and (c_2) are arbitrary constants, (y=c_1e^x+c_2e^{-x}) is a solution of Equation ef{eq:5.1.4} on ((-infty,infty)).

Solution:

a. If (y_1=e^x) then (y_1'=e^x) and (y_1''=e^x=y_1), so (y_1''-y_1=0). If (y_2=e^{-x}), then (y_2'=-e^{-x}) and (y_2''=e^{-x}=y_2), so (y_2''-y_2=0).

b. If [label{eq:5.1.6} y=c_1e^x+c_2e^{-x}] then [label{eq:5.1.7} y'=c_1e^x-c_2e^{-x}] and [y''=c_1e^x+c_2e^{-x}, onumber ]

so [egin{aligned} y''-y&=(c_1e^x+c_2e^{-x})-(c_1e^x+c_2e^{-x}) &=c_1(e^x-e^x)+c_2(e^{-x}-e^{-x})=0end{aligned} onumber ] for all (x). Therefore (y=c_1e^x+c_2e^{-x}) is a solution of Equation ef{eq:5.1.4} on ((-infty,infty)).

c.

We can solve Equation ef{eq:5.1.5} by choosing (c_1) and (c_2) in Equation ef{eq:5.1.6} so that (y(0)=1) and (y'(0)=3). Setting (x=0) in Equation ef{eq:5.1.6} and Equation ef{eq:5.1.7} shows that this is equivalent to

[egin{aligned} c_1+c_2&=1 c_1-c_2&=3.end{aligned} onumber ]

Solving these equations yields (c_1=2) and (c_2=-1). Therefore (y=2e^x-e^{-x}) is the unique solution of Equation ef{eq:5.1.5} on ((-infty,infty)).

Example (PageIndex{2})

Let (omega) be a positive constant. The coefficients of (y') and (y) in

[label{eq:5.1.8} y''+omega^2y=0]

are the constant functions (pequiv0) and (qequivomega^2), which are continuous on ((-infty,infty)). Therefore Theorem (PageIndex{1}) implies that every initial value problem for Equation ef{eq:5.1.8} has a unique solution on ((-infty,infty)).

1. Verify that (y_1=cosomega x) and (y_2=sinomega x) are solutions of Equation ef{eq:5.1.8} on ((-infty,infty)).
2. Verify that if (c_1) and (c_2) are arbitrary constants then (y=c_1cosomega x+c_2sinomega x) is a solution of Equation ef{eq:5.1.8} on ((-infty,infty)).

Solution:

a. If (y_1=cosomega x) then (y_1'=-omegasinomega x) and (y_1''=-omega^2cosomega x=-omega^2y_1), so (y_1''+omega^2y_1=0). If (y_2=sinomega x) then, (y_2'=omegacosomega x) and (y_2''=-omega^2sinomega x=-omega^2y_2), so (y_2''+omega^2y_2=0).

b. If [label{eq:5.1.10} y=c_1cosomega x+c_2sinomega x] then [label{eq:5.1.11} y'=omega(-c_1sinomega x+c_2cosomega x)] and [y''=-omega^2(c_1cosomega x+c_2sinomega x), onumber ] so [egin{aligned} y''+omega^2y&= -omega^2(c_1cosomega x+c_2sinomega x) +omega^2(c_1cosomega x+c_2sinomega x) &=c_1omega^2(-cosomega x+cosomega x)+ c_2omega^2(-sinomega x+sinomega x)=0end{aligned} onumber ] for all (x). Therefore (y=c_1cosomega x+c_2sinomega x) is a solution of Equation ef{eq:5.1.8} on ((-infty,infty)).

c. To solve Equation ef{eq:5.1.9}, we must choosing (c_1) and (c_2) in Equation ef{eq:5.1.10} so that (y(0)=1) and (y'(0)=3). Setting (x=0) in Equation ef{eq:5.1.10} and Equation ef{eq:5.1.11} shows that (c_1=1) and (c_2=3/omega). Therefore

[y=cosomega x+{3overomega}sinomega x onumber ]

is the unique solution of Equation ef{eq:5.1.9} on ((-infty,infty)).

Theorem (PageIndex{1}) implies that if (k_0) and (k_1) are arbitrary real numbers then the initial value problem

has a unique solution on an interval ((a,b)) that contains (x_0), provided that (P_0), (P_1), and (P_2) are continuous and (P_0) has no zeros on ((a,b)). To see this, we rewrite the differential equation in Equation ef{eq:5.1.12} as

[y''+{P_1(x)over P_0(x)}y'+{P_2(x)over P_0(x)}y=0 onumber ]

and apply Theorem (PageIndex{1}) with (p=P_1/P_0) and (q=P_2/P_0).

Example (PageIndex{3})

The equation

[label{eq:5.1.13} x^2y''+xy'-4y=0]

has the form of the differential equation in Equation ef{eq:5.1.12}, with (P_0(x)=x^2), (P_1(x)=x), and (P_2(x)=-4), which are are all continuous on ((-infty,infty)). However, since (P(0)=0) we must consider solutions of Equation ef{eq:5.1.13} on ((-infty,0)) and ((0,infty)). Since (P_0) has no zeros on these intervals, Theorem (PageIndex{1}) implies that the initial value problem

has a unique solution on ((0,infty)) if (x_0>0), or on ((-infty,0)) if (x_0<0).

1. Verify that (y_1=x^2) is a solution of Equation ef{eq:5.1.13} on ((-infty,infty)) and (y_2=1/x^2) is a solution of Equation ef{eq:5.1.13} on ((-infty,0)) and ((0,infty)).
2. Verify that if (c_1) and (c_2) are any constants then (y=c_1x^2+c_2/x^2) is a solution of Equation ef{eq:5.1.13} on ((-infty,0)) and ((0,infty)).

Solution:

a. If (y_1=x^2) then (y_1'=2x) and (y_1''=2), so [x^2y_1''+xy_1'-4y_1=x^2(2)+x(2x)-4x^2=0 onumber ] for (x) in ((-infty,infty)). If (y_2=1/x^2), then (y_2'=-2/x^3) and (y_2''=6/x^4), so [x^2y_2''+xy_2'-4y_2=x^2left(6over x^4 ight)-xleft(2over x^3 ight)-{4over x^2}=0 onumber ] for (x) in ((-infty,0)) or ((0,infty)).

b. If [label{eq:5.1.16} y=c_1x^2+{c_2over x^2}] then [label{eq:5.1.17} y'=2c_1x-{2c_2over x^3}] and [y''=2c_1+{6c_2over x^4}, onumber ] so [egin{aligned} x^{2}y''+xy'-4y&=x^{2}left(2c_{1}+frac{6c_{2}}{x^{4}} ight)+xleft(2c_{1}x-frac{2c_{2}}{x^{3}} ight)-4left(c_{1}x^{2}+frac{c_{2}}{x^{2}} ight) &=c_{1}(2x^{2}+2x^{2}-4x^{2})+c_{2}left(frac{6}{x^{2}}-frac{2}{x^{2}}-frac{4}{x^{2}} ight) &=c_{1}cdot 0+c_{2}cdot 0 = 0 end{aligned} onumber ] for (x) in ((-infty,0)) or ((0,infty)).

c. To solve Equation ef{eq:5.1.14}, we choose (c_1) and (c_2) in Equation ef{eq:5.1.16} so that (y(1)=2) and (y'(1)=0). Setting (x=1) in Equation ef{eq:5.1.16} and Equation ef{eq:5.1.17} shows that this is equivalent to

[egin{aligned} phantom{2}c_1+phantom{2}c_2&=2 2c_1-2c_2&=0.end{aligned} onumber ]

Solving these equations yields (c_1=1) and (c_2=1). Therefore (y=x^2+1/x^2) is the unique solution of Equation ef{eq:5.1.14} on ((0,infty)).

d. We can solve Equation ef{eq:5.1.15} by choosing (c_1) and (c_2) in Equation ef{eq:5.1.16} so that (y(-1)=2) and (y'(-1)=0). Setting (x=-1) in Equation ef{eq:5.1.16} and Equation ef{eq:5.1.17} shows that this is equivalent to

[egin{aligned} phantom{-2}c_1+phantom{2}c_2&=2 -2c_1+2c_2&=0.end{aligned} onumber ]

Solving these equations yields (c_1=1) and (c_2=1). Therefore (y=x^2+1/x^2) is the unique solution of Equation ef{eq:5.1.15} on ((-infty,0)).

Although the formulas for the solutions of Equation ef{eq:5.1.14} and Equation ef{eq:5.1.15} are both (y=x^2+1/x^2), you should not conclude that these two initial value problems have the same solution. Remember that a solution of an initial value problem is defined on an interval that contains the initial point; therefore, the solution of Equation ef{eq:5.1.14} is (y=x^2+1/x^2) on the interval ((0,infty)), which contains the initial point (x_0=1), while the solution of Equation ef{eq:5.1.15} is (y=x^2+1/x^2) on the interval ((-infty,0)), which contains the initial point (x_0=-1).

## The General Solution of a Homogeneous Linear Second Order Equation

If (y_1) and (y_2) are defined on an interval ((a,b)) and (c_1) and (c_2) are constants, then

[y=c_1y_1+c_2y_2 onumber ]

is a linear combination of (y_1) and (y_2). For example, (y=2cos x+7 sin x) is a linear combination of (y_1= cos x) and (y_2=sin x), with (c_1=2) and (c_2=7).

The next theorem states a fact that we’ve already verified in Examples (PageIndex{1}), (PageIndex{2}), (PageIndex{3}).

Theorem (PageIndex{2})

If (y_1) and (y_2) are solutions of the homogeneous equation

[label{eq:5.1.18} y''+p(x)y'+q(x)y=0]

on ((a,b),) then any linear combination

[label{eq:5.1.19} y=c_1y_1+c_2y_2]

of (y_1) and (y_2) is also a solution of (eqref{eq:5.1.18}) on ((a,b).)

Proof

If [y=c_1y_1+c_2y_2 onumber ] then [y'=c_1y_1'+c_2y_2'quad ext{ and} quad y''=c_1y_1''+c_2y_2''. onumber ]

Therefore

[egin{aligned} y''+p(x)y'+q(x)y&=(c_1y_1''+c_2y_2'')+p(x)(c_1y_1'+c_2y_2') +q(x)(c_1y_1+c_2y_2) &=c_1left(y_1''+p(x)y_1'+q(x)y_1 ight) +c_2left(y_2''+p(x)y_2'+q(x)y_2 ight) &=c_1cdot0+c_2cdot0=0,end{aligned} onumber ]

since (y_1) and (y_2) are solutions of Equation ef{eq:5.1.18}.

We say that ({y_1,y_2}) is a fundamental set of solutions of (eqref{eq:5.1.18}) on ((a,b)) if every solution of Equation ef{eq:5.1.18} on ((a,b)) can be written as a linear combination of (y_1) and (y_2) as in Equation ef{eq:5.1.19}. In this case we say that Equation ef{eq:5.1.19} is general solution of (eqref{eq:5.1.18}) on ((a,b)).

## Linear Independence

We need a way to determine whether a given set ({y_1,y_2}) of solutions of Equation ef{eq:5.1.18} is a fundamental set. The next definition will enable us to state necessary and sufficient conditions for this.

We say that two functions (y_1) and (y_2) defined on an interval ((a,b)) are linearly independent on ((a,b)) if neither is a constant multiple of the other on ((a,b)). (In particular, this means that neither can be the trivial solution of Equation ef{eq:5.1.18}, since, for example, if (y_1equiv0) we could write (y_1=0y_2).) We’ll also say that the set ({y_1,y_2}) is linearly independent on ((a,b)).

Theorem (PageIndex{3})

Suppose (p) and (q) are continuous on ((a,b).) Then a set ({y_1,y_2}) of solutions of

[label{eq:5.1.20} y''+p(x)y'+q(x)y=0]

on ((a,b)) is a fundamental set if and only if ({y_1,y_2}) is linearly independent on ((a,b).)

Proof

We’ll present the proof of Theorem (PageIndex{3}) in steps worth regarding as theorems in their own right. However, let’s first interpret Theorem (PageIndex{3}) in terms of Examples (PageIndex{1}), (PageIndex{2}), (PageIndex{3}).

Example (PageIndex{4})

Since (e^x/e^{-x}=e^{2x}) is nonconstant, Theorem (PageIndex{3}) implies that (y=c_1e^x+c_2e^{-x}) is the general solution of (y''-y=0) on ((-infty,infty)).

Since (cosomega x/sinomega x=cotomega x) is nonconstant, Theorem (PageIndex{3}) implies that (y=c_1cosomega x+c_2sinomega x) is the general solution of (y''+omega^2y=0) on ((-infty,infty)).

Since (x^2/x^{-2}=x^4) is nonconstant, Theorem (PageIndex{3}) implies that (y=c_1x^2+c_2/x^2) is the general solution of (x^2y''+xy'-4y=0) on ((-infty,0)) and ((0,infty)).

## The Wronskian and Abel's Formula

To motivate a result that we need in order to prove Theorem (PageIndex{3}), let’s see what is required to prove that ({y_1,y_2}) is a fundamental set of solutions of Equation ef{eq:5.1.20} on ((a,b)). Let (x_0) be an arbitrary point in ((a,b)), and suppose (y) is an arbitrary solution of Equation ef{eq:5.1.20} on ((a,b)). Then (y) is the unique solution of the initial value problem

that is, (k_0) and (k_1) are the numbers obtained by evaluating (y) and (y') at (x_0). Moreover, (k_0) and (k_1) can be any real numbers, since Theorem (PageIndex{1}) implies that Equation ef{eq:5.1.21} has a solution no matter how (k_0) and (k_1) are chosen. Therefore ({y_1,y_2}) is a fundamental set of solutions of Equation ef{eq:5.1.20} on ((a,b)) if and only if it is possible to write the solution of an arbitrary initial value problem Equation ef{eq:5.1.21} as (y=c_1y_1+c_2y_2). This is equivalent to requiring that the system

[label{eq:5.1.22} egin{array}{rcl} c_1y_1(x_0)+c_2y_2(x_0)&=k_0 c_1y_1'(x_0)+c_2y_2'(x_0)&=k_1 end{array}]

has a solution ((c_1,c_2)) for every choice of ((k_0,k_1)). Let’s try to solve Equation ef{eq:5.1.22}.

Multiplying the first equation in Equation ef{eq:5.1.22} by (y_2'(x_0)) and the second by (y_2(x_0)) yields

[egin{aligned} c_1y_1(x_0)y_2'(x_0)+c_2y_2(x_0)y_2'(x_0)&= y_2'(x_0)k_0 c_1y_1'(x_0)y_2(x_0)+c_2y_2'(x_0)y_2(x_0)&= y_2(x_0)k_1,end{aligned}]

and subtracting the second equation here from the first yields

[label{eq:5.1.23} left(y_1(x_0)y_2'(x_0)-y_1'(x_0)y_2(x_0) ight)c_1= y_2'(x_0)k_0-y_2(x_0)k_1.]

Multiplying the first equation in Equation ef{eq:5.1.22} by (y_1'(x_0)) and the second by (y_1(x_0)) yields

[egin{aligned} c_1y_1(x_0)y_1'(x_0)+c_2y_2(x_0)y_1'(x_0)&= y_1'(x_0)k_0 c_1y_1'(x_0)y_1(x_0)+c_2y_2'(x_0)y_1(x_0)&= y_1(x_0)k_1,end{aligned}]

and subtracting the first equation here from the second yields

[label{eq:5.1.24} left(y_1(x_0)y_2'(x_0)-y_1'(x_0)y_2(x_0) ight)c_2= y_1(x_0)k_1-y_1'(x_0)k_0.]

If

[y_1(x_0)y_2'(x_0)-y_1'(x_0)y_2(x_0)=0, onumber ]

it is impossible to satisfy Equation ef{eq:5.1.23} and Equation ef{eq:5.1.24} (and therefore Equation ef{eq:5.1.22} ) unless (k_0) and (k_1) happen to satisfy

[egin{aligned} y_1(x_0)k_1-y_1'(x_0)k_0&=0 y_2'(x_0)k_0-y_2(x_0)k_1&=0.end{aligned}]

On the other hand, if

[label{eq:5.1.25} y_1(x_0)y_2'(x_0)-y_1'(x_0)y_2(x_0) e0]

we can divide Equation ef{eq:5.1.23} and Equation ef{eq:5.1.24} through by the quantity on the left to obtain

[label{eq:5.1.26} egin{array}{rcl} c_1&={y_2'(x_0)k_0-y_2(x_0)k_1over y_1(x_0)y_2'(x_0)-y_1'(x_0)y_2(x_0)} c_2&={y_1(x_0)k_1-y_1'(x_0)k_0over y_1(x_0)y_2'(x_0)-y_1'(x_0)y_2(x_0)}, end{array}]

no matter how (k_0) and (k_1) are chosen. This motivates us to consider conditions on (y_1) and (y_2) that imply Equation ef{eq:5.1.25}.

Theorem (PageIndex{4})

Suppose (p) and (q) are continuous on ((a,b),) let (y_1) and (y_2) be solutions of

[label{eq:5.1.27} y''+p(x)y'+q(x)y=0]

on ((a,b)), and define

[label{eq:5.1.28} W=y_1y_2'-y_1'y_2.]

Let (x_0) be any point in ((a,b).) Then

Therefore either (W) has no zeros in ((a,b)) or (Wequiv0) on ((a,b).)

Proof

Differentiating Equation ef{eq:5.1.28} yields

[label{eq:5.1.30} W'=y'_1y'_2+y_1y''_2-y'_1y'_2-y''_1y_2= y_1y''_2-y''_1y_2.]

Since (y_1) and (y_2) both satisfy Equation ef{eq:5.1.27},

Substituting these into Equation ef{eq:5.1.30} yields

[egin{aligned} W'&= -y_1igl(py'_2+qy_2igr) +y_2igl(py'_1+qy_1igr) &= -p(y_1y'_2-y_2y'_1)-q(y_1y_2-y_2y_1) &= -p(y_1y'_2-y_2y'_1)=-pW.end{aligned} onumber ]

Therefore (W'+p(x)W=0); that is, (W) is the solution of the initial value problem

We leave it to you to verify by separation of variables that this implies Equation ef{eq:5.1.29}. If (W(x_0) e0), Equation ef{eq:5.1.29} implies that (W) has no zeros in ((a,b)), since an exponential is never zero. On the other hand, if (W(x_0)=0), Equation ef{eq:5.1.29} implies that (W(x)=0) for all (x) in ((a,b)).

The function (W) defined in Equation ef{eq:5.1.28} is the Wronskian of ({y_1,y_2}). Formula Equation ef{eq:5.1.29} is Abel’s formula.

The Wronskian of ({y_1,y_2}) is usually written as the determinant

[W=left| egin{array}{cc} y_1 & y_2 y'_1 & y'_2 end{array} ight|. onumber ]

The expressions in Equation ef{eq:5.1.26} for (c_1) and (c_2) can be written in terms of determinants as

[c_1={1over W(x_0)} left| egin{array}{cc} k_0 & y_2(x_0) k_1 & y'_2(x_0) end{array} ight| quad ext{and} quad c_2={1over W(x_0)} left| egin{array}{cc} y_1(x_0) & k_0 y'_1(x_0) &k_1 end{array} ight|. onumber ]

If you’ve taken linear algebra you may recognize this as Cramer’s rule.

Example (PageIndex{5})

Verify Abel’s formula for the following differential equations and the corresponding solutions, from Examples (PageIndex{1}), (PageIndex{2}), (PageIndex{3}).

2. (y''+omega^2y=0;quad y_1=cosomega x,; y_2=sinomega x)

Solution:

a. Since (pequiv0), we can verify Abel’s formula by showing that (W) is constant, which is true, since

[W(x)=left| egin{array}{rr} e^x & e^{-x} e^x & -e^{-x} end{array} ight|=e^x(-e^{-x})-e^xe^{-x}=-2 onumber ]

for all (x).

b. Again, since (pequiv0), we can verify Abel’s formula by showing that (W) is constant, which is true, since

[egin{aligned} W(x)&={left| egin{array}{cc} cosomega x & sinomega x -omegasinomega x &omegacosomega x end{array} ight|} &=cosomega x (omegacosomega x)-(-omegasinomega x)sinomega x &=omega(cos^2omega x+sin^2omega x)=omegaend{aligned} onumber ]

for all (x).

c. Computing the Wronskian of (y_1=x^2) and (y_2=1/x^2) directly yields

[label{eq:5.1.31} W=left| egin{array}{cc} x^2 & 1/x^2 2x & -2/x^3 end{array} ight|=x^2left(-{2over x^3} ight)-2xleft(1over x^2 ight)=-{4over x}.]

To verify Abel’s formula we rewrite the differential equation as

[y''+{1over x}y'-{4over x^2}y=0 onumber ]

to see that (p(x)=1/x). If (x_0) and (x) are either both in ((-infty,0)) or both in ((0,infty)) then

[int_{x_0}^x p(t),dt=int_{x_0}^x {dtover t}=lnleft(xover x_0 ight), onumber ]

so Abel’s formula becomes

[egin{aligned} W(x)&=W(x_0)e^{-ln(x/x_0)}=W(x_0){x_0over x} &=-left(4over x_0 ight)left(x_0over x ight)quad ext{from} eqref{eq:5.1.31} &=-{4over x},end{aligned} onumber ]

which is consistent with Equation ef{eq:5.1.31}.

The next theorem will enable us to complete the proof of Theorem (PageIndex{3}).

Theorem (PageIndex{5})

Suppose (p) and (q) are continuous on an open interval ((a,b),) let (y_1) and (y_2) be solutions of

[label{eq:5.1.32} y''+p(x)y'+q(x)y=0]

on ((a,b),) and let (W=y_1y_2'-y_1'y_2.) Then (y_1) and (y_2) are linearly independent on ((a,b)) if and only if (W) has no zeros on ((a,b).)

Proof

We first show that if (W(x_0)=0) for some (x_0) in ((a,b)), then (y_1) and (y_2) are linearly dependent on ((a,b)). Let (I) be a subinterval of ((a,b)) on which (y_1) has no zeros. (If there’s no such subinterval, (y_1equiv0) on ((a,b)), so (y_1) and (y_2) are linearly independent, and we are finished with this part of the proof.) Then (y_2/y_1) is defined on (I), and

[label{eq:5.1.33} left(y_2over y_1 ight)'={y_1y_2'-y_1'y_2over y_1^2}={Wover y_1^2}.]

However, if (W(x_0)=0), Theorem (PageIndex{4}) implies that (Wequiv0) on ((a,b)). Therefore Equation ef{eq:5.1.33} implies that ((y_2/y_1)'equiv0), so (y_2/y_1=c) (constant) on (I). This shows that (y_2(x)=cy_1(x)) for all (x) in (I). However, we want to show that (y_2=cy_1(x)) for all (x) in ((a,b)). Let (Y=y_2-cy_1). Then (Y) is a solution of Equation ef{eq:5.1.32} on ((a,b)) such that (Yequiv0) on (I), and therefore (Y'equiv0) on (I). Consequently, if (x_0) is chosen arbitrarily in (I) then (Y) is a solution of the initial value problem

which implies that (Yequiv0) on ((a,b)), by the paragraph following Theorem (PageIndex{1}). (See also Exercise 5.1.24). Hence, (y_2-cy_1equiv0) on ((a,b)), which implies that (y_1) and (y_2) are not linearly independent on ((a,b)).

Now suppose (W) has no zeros on ((a,b)). Then (y_1) can’t be identically zero on ((a,b)) (why not?), and therefore there is a subinterval (I) of ((a,b)) on which (y_1) has no zeros. Since Equation ef{eq:5.1.33} implies that (y_2/y_1) is nonconstant on (I), (y_2) isn’t a constant multiple of (y_1) on ((a,b)). A similar argument shows that (y_1) isn’t a constant multiple of (y_2) on ((a,b)), since

[left(y_1over y_2 ight)'={y_1'y_2-y_1y_2'over y_2^2}=-{Wover y_2^2} onumber ]

on any subinterval of ((a,b)) where (y_2) has no zeros.

We can now complete the proof of Theorem (PageIndex{3}). From Theorem (PageIndex{5}), two solutions (y_1) and (y_2) of Equation ef{eq:5.1.32} are linearly independent on ((a,b)) if and only if (W) has no zeros on ((a,b)). From Theorem (PageIndex{4}) and the motivating comments preceding it, ({y_1,y_2}) is a fundamental set of solutions of Equation ef{eq:5.1.32} if and only if (W) has no zeros on ((a,b)). Therefore ({y_1,y_2}) is a fundamental set for Equation ef{eq:5.1.32} on ((a,b)) if and only if ({y_1,y_2}) is linearly independent on ((a,b)).

The next theorem summarizes the relationships among the concepts discussed in this section.

Theorem (PageIndex{6})

Suppose (p) and (q) are continuous on an open interval ((a,b)) and let (y_1) and (y_2) be solutions of

[label{eq:5.1.34} y''+p(x)y'+q(x)y=0]

on ((a,b).) Then the following statements are equivalent(;) that is(,) they are either all true or all false(.)

1. The general solution of (eqref{eq:5.1.34}) on ((a,b)) is (y=c_1y_1+c_2y_2).
2. ({y_1,y_2}) is a fundamental set of solutions of (eqref{eq:5.1.34}) on ((a,b).)
3. ({y_1,y_2}) is linearly independent on ((a,b).)
4. The Wronskian of ({y_1,y_2}) is nonzero at some point in ((a,b).)
5. The Wronskian of ({y_1,y_2}) is nonzero at all points in ((a,b).)

We can apply this theorem to an equation written as

[P_0(x)y''+P_1(x)y'+P_2(x)y=0 onumber ]

on an interval ((a,b)) where (P_0), (P_1), and (P_2) are continuous and (P_0) has no zeros.dd proof here and it will automatically be hidden

Theorem (PageIndex{7})

Suppose (c) is in ((a,b)) and (alpha) and (eta) are real numbers, not both zero. Under the assumptions of Theorem (PageIndex{7}), suppose (y_{1}) and (y_{2}) are solutions of Equation ef{eq:5.1.34} such that